EFEKTIVITAS FLIPPED CLASSROOM TERHADAP KEMAMPUAN PEMAHAMAN KONSEP DAN BERPIKIR KRITIS MATEMATIS: SYSTEMTIC LITERATURE REVIEW - Novita Fatmiyati; Dadang Juandi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aimed to analyze the effects of flipped classroom model on students’ conceptual understanding and critical thinking in mathematics learning. The method used in this research is a Systematic Literature Review. The search process is adjusted to inclusion criteria and based on PRISMA protocol. The data analysis techniques of this research include identifying, assessing or evaluating, and making conclusion. The results found in this study are (1) there is an effect of applying flipped classroom model on students’ conceptual understanding and critical thinking, (2) there is heterogeneity in research on the effect of applying flipped classroom model on students’ conceptual understanding and critical thinking, (3) the most used learning media is the video as a learning tool, (4) flipped classroom model becomes one of learning alternatives that can be used to enhance students’ conceptual understanding ability and critcal thinking.